SsMet1 is a critical gene in methionine biosynthesis in Sclerotinia sclerotiorum - Pierre-Pierre, Nickisha; Wei, Wei; Manasseh, Richard; Mendoza, Michelle; Vandemark, George J.; Chen, Weidong (Frontiers in Fungal Biology, 2025)
Methionine, a key sulfur-containing amino acid, is involved in various important functions in cellular metabolism. Genes that encode enzymes to catalyze steps of the methionine biosynthesis pathway are essential for survival of fungi. The SsMet1 (SS1G_11000) gene in Sclerotinia sclerotiorum is an orthologue of BcStr2, a gene characterized in Botrytis cinerea that plays a key role in methionine biosynthesis. In this study, we characterized SsMet1 in S. sclerotiorum by creating SsMet1-deletion mutants, Met1–2 and Met1-4, using a split marker technique. The SsMet1-deletion mutants were unable to grow on minimal medium and did not produce sclerotia. Supplementation with methionine and homocysteine rescued the defects in mycelial growth, but not sclerotial development of the SsMet1-deletion mutants. These results indicate that SsMet1-deletion mutants are auxotrophic for methionine. In addition, the SsMet1-deletion mutants exhibited increased sensitivity to osmotic and oxidative stresses, cell wall-damaging agents, and thermal stress. The mutants were avirulent on detached bean leaves, but virulence was also restored with methionine supplementation in minimal media. All the defects were restored by genetic complementation of the mutant with wildtype SsMet1 allele. The results of this study indicate that SsMet1 plays a critical role in the regulation of various cellular processes in S. sclerotiorum.